Comparing efficacy and safety in catheter ablation strategies for atrial fibrillation: protocol of a network meta-analysis of randomised controlled trials. Issue 11 (23rd November 2020) - Charitakis, Emmanouil; Karlsson, Lars O; Rizas, Kostantinos; Almroth, Henrik; Hassel Jönsson, Anders; Schweiler, Jonas; Sideris, Skevos; Tsartsalis, Dimitrios; Dragioti, Elena; Chaimani, Anna
Abstract : Introduction: Atrial fibrillation (AF) is the most common sustained arrhythmia. Catheter ablation (CA) of AF is an increasingly offered therapeutic approach, primary to relieve AF-related symptoms. Despite the development of new ablation approaches, there is no consensus regarding the most efficient ablation strategy. The objective of this network meta-analysis (NMA) is to compare the efficacy and safety of all different CA approaches for the treatment of patients with paroxysmal (PAF) and non-PAF (non-PAF). Methods and analysis: We will perform a systematic search to identify randomised controlled trials of different CA approaches for the treatment of PAF and non-PAF, through the final search date of 1 March 2020. Information sources will include major bibliographic databases (MEDLINE, Web of Science and CENTRAL) and clinical trial registries. Our primary outcomes will be the efficacy (recurrence-free survival) and safety of different CA approaches for the treatment of AF. Secondary outcomes will be all-cause mortality and procedural time. An NMA will be performed to determine the relative effects of different catheter ablation approaches (such as pulmonary vein isolation alone or in combination with ablation lines, ablation of complex fractionated atrial electrograms, etc). In PAF, a separate analysis will be performed including different energy sources (such as radiofrequency, cryogenic and laser energy). Risk of bias assessment and sensitivity analyses will be conducted to assess the robustness of the findings to potential bias. Ethics and dissemination: No ethical approval will be needed because data are collected from previous studies. The results will be presented through peer-review journals and conference presentation. PROSPERO registration number: CRD42020169494.